Anti-Inflammatory Effect of Cinnamomum japonicum Siebold's Leaf through the Inhibition of p38/JNK/AP-1 Signaling - Ji Min Kim; In A Jung; Jae Min Kim; Moon-Hee Choi; Ji Hye Yang (MDPI AG, 2023)
Cinnamomum japonicum Siebold (CJ) branch bark, commonly known as Japanese cinnamon, has been used for various culinary and medicinal applications for many centuries. Although the efficacy of CJ branch bark's anti-inflammatory and antioxidant activity for the treatment of various diseases has been confirmed, the efficacy of CJ leaves (CJLs) has not been examined. We therefore investigated whether CJL3, an ethyl acetate extract of a 70% ethanol CJL extract, exerts anti-inflammatory effects on lipopolysaccharide (LPS)-activated Kupffer cells, specialized macrophages found in the liver. Liver inflammation can activate Kupffer cells, inducing the release of pro-inflammatory molecules that contribute to tissue damage. We found that CJL3 has high 2,2-diphenyl-1-picrylhydrazyl and 2,2-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) radical-scavenging activity. Among the CJL extracts, CJL3 exhibited the greatest polyphenol content, with protocatechuic acid and 4-hydroxybenzoic acid being the most abundant. In addition, we verified that CJL3, which has strong antioxidant properties, ameliorates LPS-induced pro-inflammatory responses by inhibiting p38/JNK/AP-1 signaling. CJL3 therefore has potential for treating liver disease, including hepatitis.